2020
DOI: 10.3390/microorganisms8122024
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Petrimonas mucosa ING2-E5AT in Mesophilic Biogas Reactor Systems as Deduced from Multiomics Analyses

Abstract: Members of the genera Proteiniphilum and Petrimonas were speculated to represent indicators reflecting process instability within anaerobic digestion (AD) microbiomes. Therefore, Petrimonas mucosa ING2-E5AT was isolated from a biogas reactor sample and sequenced on the PacBio RSII and Illumina MiSeq sequencers. Phylogenetic classification positioned the strain ING2-E5AT in close proximity to Fermentimonas and Proteiniphilum species (family Dysgonomonadaceae). ING2-E5AT encodes a number of genes for glycosyl-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 87 publications
1
15
0
Order By: Relevance
“…When analyzing the top 25 genera, only four genera were shared between WW and PF of which three were unclassified ( Supplementary Figure 4 ). A recent meta-omics study on the genus Petrimonas revealed its function in sugar and amino acid fermentation pathways and its widespread occurrence in biogas reactors, particularly in biogas plants with process disorders ( Maus et al, 2020 ). The dominance of this genus in the WW and PF communities might be related to microbial biomass turnover under stress conditions such as substrate shift in phase 1 and starvation in phases 2–5.…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing the top 25 genera, only four genera were shared between WW and PF of which three were unclassified ( Supplementary Figure 4 ). A recent meta-omics study on the genus Petrimonas revealed its function in sugar and amino acid fermentation pathways and its widespread occurrence in biogas reactors, particularly in biogas plants with process disorders ( Maus et al, 2020 ). The dominance of this genus in the WW and PF communities might be related to microbial biomass turnover under stress conditions such as substrate shift in phase 1 and starvation in phases 2–5.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the distribution and abundance of the phage genomes in different biogas communities, fragment recruitments were performed. To this end, the tool SparkHit [52] was used as described previously [53] and genome sequences of each MAVG were employed as a template. Corresponding computations were scaled-up and parallelized by using the de.NBI Cloud environment (https://www.denbi.de/cloud, accessed on 12 September 2021).…”
Section: Fragment Recruitmentmentioning
confidence: 99%
“…To identify additional MD1 T variant strains in biogas-producing microbial communities, metagenome fragment recruitments using the genome sequence of MD1 T as template were performed using SparkHit [45] as described previously [46]. Corresponding computations were scaled up and parallelized by using the de.NBI Cloud environment (www.denbi.de/cloud).…”
Section: Genome Featuresmentioning
confidence: 99%